Activation of proteinase-activated receptor-2 (PAR-2) simultaneously induces interleukin 8 (IL-8) and suppresses monocyte chemoattractant protein-1 (MCP-1) in HaCaT cells - Murakami, Yoshinobu; Azuma, Seisho; Baba, Kimiye; Taniguchi, Masahiko; Furukawa, Fukumi (Trends in Immunotherapy, 2022)
Allergic diseases are currently considered diseases of excessive type 2 inflammation created by orchestration between the innate and acquired immune systems. Since pattern recognition receptors (PRRs) are present in epidermal keratinocytes, it is noteworthy that aggravating factors of allergic diseases act directly on keratinocytes via PRRs. To investigate the relationship between the activation of PRRs and inflammation, we stimulated a keratinocyte cell line (HaCaT cells) with agonists against proteinase-activated receptor-2 (PAR-2), Toll-like receptor (TLR)2, and TLR4, alone or in combination, and we evaluated the changes in inflammatory cytokines and chemokines. Activation of TLR2 or TLR4 alone induced interleukin 6 (IL-6), IL-8, and monocyte chemoattractant protein-1 (MCP-1) in an agonist concentration-dependent manner. Simultaneous activation of TLR2 and TLR4 induced IL-8 synergistically, MCP-1 in an additive trend, and IL-6 weakly but synergistically. PAR-2 activation of HaCaT cells induced IL-6 and IL-8 but suppressed MCP-1 in an agonist concentration-dependent manner. The enhancement of IL-8 and the suppression of MCP-1 by PAR-2 activation were both neutralized by the PAR-2 antagonist AZ3451, supporting the possibility that PAR-2 activation simultaneously induces the following opposing effects in inflammation: enhancement of IL-8 and suppression of MCP-1. The nuclear factor-κB (NF-κB) pathway inhibitor BAY 11-7082 neutralized the induction of IL-8 but not the suppression of MCP-1 by PAR-2 activation, indicating that PAR-2 activation induces activation of the NF-κB pathway, and that the suppression of MCP-1 by PAR-2 activation is not related to the NF-κB pathway.